Maturity Model of Response Protocols to Ransomware Scenarios in the Mining Sector - Gomez, Brignith (2024)
The Maturity Model for Defense Protocols against Ransomware Scenarios in the mining sector is a useful tool to assess an organization’s level of preparedness against ransomware attacks and design effective strategies to mitigate their impacts. This model, based on the NIST methodology and the ISO 27001 AND 27002 Standards, and the experience of cybersecurity experts, consists of five levels of maturity that go from initial adoption to defense optimization. The Initial level focuses on risk awareness and basic preparation. The Managed level focuses on the protection of critical data and systems, while the Defined level, focuses on early detection and response to incidents. The Managed level seeks response automation and collaboration with third parties, while Optimized level, focuses on continuous improvement and innovation. For each level, achieve the characteristics and objectives allow organizations to assess their current position and establish action plans to improve their readiness. Some recommended best practices include ongoing employee training, implementing technical security measures, conducting incident simulations, adopting backup and recovery solutions, and collaborating with cybersecurity service providers. In summary, the Maturity Model for Ransomware Defense Protocols is a valuable tool to help organizations improve their ability to resist and recover from ransomware attacks. Its focus on best practices and continuous improvement makes it a reference in the field of cybersecurity.